2019
DOI: 10.1101/516369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular design, optimization and genomic integration of chimeric B cell receptors in murine B cells

Abstract: 15Immune cell therapies based on the integration of synthetic antigen receptors provide 16 a powerful strategy for the treatment of diverse diseases, most notably retargeting 17 T cells engineered to express chimeric antigen receptors (CAR) for cancer therapy. In 18 addition to T lymphocytes, B lymphocytes may also represent valuable immune cells 19 that can be engineered for therapeutic purposes such as protein replacement therapy 20 or recombinant antibody production. In this article, we report a promisin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…Hung et al (18) inserted therapeutic protein transgenes under the control of exogenous promoters into the CCR5 safe harbor locus as this locus is not transcriptionally active in human B cells, it is not required for plasma cell differentiation, and null mutations are innocuous to humans. In a unique BCR editing approach, Pesch et al (19) modified murine B cells for the expression of a novel chimeric BCR (CBCR), at the Rosa26 safe harbor locus. A single-chain variable fragment acting as the extracellular Ag binding domain was joined to the CD28 transmembrane domain, and the cytoplasmic domain of the endogenous murine BCR was fused to the CD79b intracellular signaling domain via a spacer encoding a Strep tag.…”
Section: B Cell Genome-editing Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hung et al (18) inserted therapeutic protein transgenes under the control of exogenous promoters into the CCR5 safe harbor locus as this locus is not transcriptionally active in human B cells, it is not required for plasma cell differentiation, and null mutations are innocuous to humans. In a unique BCR editing approach, Pesch et al (19) modified murine B cells for the expression of a novel chimeric BCR (CBCR), at the Rosa26 safe harbor locus. A single-chain variable fragment acting as the extracellular Ag binding domain was joined to the CD28 transmembrane domain, and the cytoplasmic domain of the endogenous murine BCR was fused to the CD79b intracellular signaling domain via a spacer encoding a Strep tag.…”
Section: B Cell Genome-editing Strategiesmentioning
confidence: 99%
“…A single-chain variable fragment acting as the extracellular Ag binding domain was joined to the CD28 transmembrane domain, and the cytoplasmic domain of the endogenous murine BCR was fused to the CD79b intracellular signaling domain via a spacer encoding a Strep tag. CBCRs could potentially offer a way to activate engineered B cells in an Ag-controllable manner (by vaccination), independent of the endogenous BCR (19). Luo et al (20) targeted an antiPD-1 Ab cassette to the GAPDH locus in mouse primary B cells for coexpression of the transgene along with the GAPDH enzyme.…”
Section: B Cell Genome-editing Strategiesmentioning
confidence: 99%
“…Although integration was achieved, editing efficiencies for this strategy remained extremely low at less than 0.1%. Although not directly integrating antibodies, another study attempted to engineer murine B cells to express chimeric BCRs to sense antigen and in response secrete a protein of interest ( Pesch et al., 2019 ). Similar to other studies, it was found that HDR editing rates using the conventional B cell ex vivo culture protocol and dsDNA transfection was very low at less than 1%.…”
Section: Introductionmentioning
confidence: 99%
“…HDR is currently considered the most accurate GE strategy and therefore, it is the strategy of choice for several groups. HDR has been studied for the development of gene therapy treatments for cancer [ 17 , 18 ] and several genetic diseases such as beta-haemoglobinopathies [ 19 , 20 ], primary immunodeficiencies (PID) [ 21 , 22 ], and metabolic storage disorders [ 23 , 24 ]. However, there are several limitations in the HDR strategies that preclude its clinical translation, including low efficiency in some relevant target cells, as HDR only occurs in late S/G2 phase [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%